(untitled) (Fiep Bulletin - online, 2015)
Objective: identify the occurrence of work-related accidents in the civil construction in the municipality of São José de Piranhas, Paraiba. Methodology: exploratory and descriptive field research with quantitative approach. Participated in the research 40 civil construction workers of the urban area of São José de Piranhas – PB, being adopted non-probability sampling by convenience. For the data collection, a questionnaire was used and the data was analyzed through descriptive statistics. Results: The sample was composed predominantly by men (95%), young adults (50%) (age group between 28-40 year-olds), with low levels of education (88% - illiterate, complete and incomplete elementary education). Their average income was of up to 2 minimum wages (82%), and they had been working in the sector for up to the maximum of 10 years (73%).Furthermore, 75% of the workers had already suffered accidents during the process of working in the civil construction and, in general, the accidents happened with scaffolding (20%) and 34% of the lesions were cuts. 75% of the researched workers stated that they did not use individual protection equipment. Conclusion: the civil construction worker is still exposed to the risks of accidents in the building sites, evidenced by the fact that the majority of the workers researched had already suffered some kind of work-related accident. Considering the criticality of this result, it is necessary to intervene in the labour process in the sector, adopting safety measures and education for work.